Global metabolic reprogramming of colorectal cancer occurs at adenoma stage and is induced by MYC - Satoh, Kiyotoshi; Yachida, Shinichi; Sugimoto, Masahiro; Oshima, Minoru; Nakagawa, Toshitaka; Akamoto, Shintaro; Tabata, Sho; Saitoh, Kaori; Kato, Keiko; Sato, Saya; Igarashi, Kaori; Aizawa, Yumi; et al. (Proceedings of the National Academy of Sciences - PNAS, 2017)
Cancer cells alter their metabolism for the production of precursors of macromolecules. However, the control mechanisms underlying this reprogramming are poorly understood. Here we show that metabolic reprogramming of colorectal cancer is caused chiefly by aberrant MYC expression. Multiomics-based analyses of paired normal and tumor tissues from 275 patients with colorectal cancer revealed that metabolic alterations occur at the adenoma stage of carcinogenesis, in a manner not associated with specific gene mutations involved in colorectal carcinogenesis. MYC expression induced at least 215 metabolic reactions by changing the expression levels of 121 metabolic genes and 39 transporter genes. Further, MYC negatively regulated the expression of genes involved in mitochondrial biogenesis and maintenance but positively regulated genes involved in DNA and histone methylation. Knockdown of MYC in colorectal cancer cells reset the altered metabolism and suppressed cell growth. Moreover, inhibition of MYC target pyrimidine synthesis genes such as CAD, UMPS, and CTPS blocked cell growth, and thus are potential targets for colorectal cancer therapy.